Increased level of advanced glycation end-products in renal transplant patients is associated with decreased measured GFR and grafted kidney function - Heshmatolah Shahbazian; Samaneh Salehipour Bavarsad; Hamid Yaghooti; Seyyed Mostafa Saadati; Samaneh Olapour (Journal of Nephropathology, 2019)
Background: Advanced glycation end-products (AGEs) cause proinflammatory responses and macromolecular damages. Advanced oxidation protein products (AOPPs) are protein biomarkers for oxidative stress. Levels of AGEs and AOPPs increase with the progression of chronic renal dysfunction. Objectives: In this study, we aimed to measure these species in patients with renal transplantation and to analyze their correlation with the measured glomerular filtration rate (GFR) and renal function parameters. Patients and Methods: Eighty renal transplant patients and normal subjects were recruited. GFR was measured by the two-sample plasma method with technetium-99m-labeled diethylenetriaminepentaacetic acid (TC99m-DTPA) clearance. Biochemical measurements included creatinine, cystatin C, urea, total protein, and pentosidine. Serum AGEs were determined using a fluorometric assay and AOPPs were estimated spectrophotometrically. Results: The measured GFR found to be significantly decreased in renal transplant patients compared to the control subjects (P< 0.001). Levels of AGEs, AOPPs, serum creatinine, and cystatin C were increased in renal transplant patients with lower values of measured GFR (mGFR). A significant association between the levels of AGEs species (serum fluorescence and pentosidine) and mGFR when adjusted for creatinine and other risk factors in multiple linear regression model analysis was found (P=0.05 and P=0.001, respectively). Conclusions: This study demonstrated increased levels of pentosidine and AGEs in transplant recipients were associated with decreased mGFR. Their accumulation can be predictive for the progression of chronic allograft loss of function.